2019
DOI: 10.1177/2158244019854644
|View full text |Cite
|
Sign up to set email alerts
|

Reviewing the Domain of Technology and Innovation Management: A Visualizing Bibliometric Analysis

Abstract: Technology and innovation management (TIM) plays an increasingly important role in the survival and prosperity of firms and economic growth of countries, which makes it increasingly important to trace the trajectory of this research field. However, to date, few studies have analyzed the evolution of the field of TIM quantitatively. Aiming to achieve an overall understanding of the research in the field of TIM, this study extracts all publications in the top 13 journals on TIM and their references that could be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
25
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(26 citation statements)
references
References 48 publications
1
25
0
Order By: Relevance
“…Citation data is available for a wide range of publications on ISI Web's most renowned science academic database, the WoS was suitable for this as one of the main purposes of interdisciplinary literary research and many important bibliometric studies have used this database before (Fetscherin & Usunier, 2012). The WoS database provides extensive coverage of the social sciences, and arts and humanities have previously been used in a wide range of bibliographic research (Danvila-del-Valle et al, 2019;Gurzki & Woisetschläger, 2017;Huang et al, 2019;Mulet-Forteza et al, 2019).…”
Section: Data Source and Proceduresmentioning
confidence: 99%
“…Citation data is available for a wide range of publications on ISI Web's most renowned science academic database, the WoS was suitable for this as one of the main purposes of interdisciplinary literary research and many important bibliometric studies have used this database before (Fetscherin & Usunier, 2012). The WoS database provides extensive coverage of the social sciences, and arts and humanities have previously been used in a wide range of bibliographic research (Danvila-del-Valle et al, 2019;Gurzki & Woisetschläger, 2017;Huang et al, 2019;Mulet-Forteza et al, 2019).…”
Section: Data Source and Proceduresmentioning
confidence: 99%
“…Such maps allow several aspects of a scientific field to be monitored (Noyons et al, 1999; Su et al, 2019), providing a clearer view of the results obtained (Merigó et al, 2016). Keyword co-occurrence refers to the most common keywords used to develop a research field or a scientific document (Callon et al, 1983; Ding et al, 2001; Huang et al, 2019; McCain, 1986, 1991; Zhang et al, 2019), while co-citation assumes that there is some kind of association between two documents jointly cited by a different third one (Boyack & Klavans, 2014; Hoque et al, 2021; McCain, 1990; Ramos-Rodríguez & Ruíz-Navarro, 2004; Small, 1973).…”
Section: Methodsmentioning
confidence: 99%
“…Bibliometrics entails the quantification of academic production based on certain classifications that project indirect indications on its perception (Huang et al, 2019). Multiple definitions of the term exist, although the modern version is usually attributed to Alan Pritchard.…”
Section: Bibliometrics and Social Network Analysismentioning
confidence: 99%
“…The advantage of VOSviewer is that it can be employed to process big bibliographic data sets. It is particularly useful for analysing large numbers of bibliographic objects (over a hundred items) [9][10][11][12]. The smart processing of scientific databases normalizes the links between the keywords so as to create maps [12our results showed that a comprehensive bibliometric and visualization investigation was required.…”
Section: Methodsmentioning
confidence: 99%